Bidirectional linkage between inflation and inflation uncertainty – the case of Eastern European countries - Dejan Živkov; Jovan Njegic; Marko Pecanac (Baltic Journal of Economics, 2014)
This paper explores bidirectional linkage between inflation and its uncertainty by observing monthly data of 11 Eastern European countries. The methodological approach comprises two steps. First, inflation uncertainty series have been created by choosing an optimal Generalized Autoregressive Conditional Heteroskedasticity- (GARCH) type model. Subsequently, inflation and inflation uncertainty have been observed together by two models examining whether Friedman's and Cukierman–Meltzer's hypotheses hold for selected Eastern Europe Countries (EEC). Due to the heterogeneous behaviour of some series of inflation and inflation uncertainty, the unconditional quantile regression estimation technique has been applied because of its robustness to the particular non-normal characteristics and outliers' presence in the empirical data. According to the findings, both Friedman's and Cukierman–Meltzer's hypotheses have been confirmed primarily for the largest EEC with flexible exchange rate. In contrast, these theories are refuted in smaller, open economies with firm exchange rate regime.
Keywords: C32; C51; E31; 330; inflation; inflation uncertainty; GARCH; quantile regression; Eastern European countries